Pectin-alginate does not further enhance exogenous carbohydrate oxidation in running - Barber, J.; Thomas, J.; Narang, B.; Hengist, A.; Betts, J. A.; Wallis, G. A.; Gonzalez, J. T. (Medicine & Science in Sports & Exercise, 2020)
Purpose: Maximizing carbohydrate availability is important for many endurance events. Combining pectin and sodium alginate with ingested maltodextrin-fructose (MAL + FRU + PEC + ALG) has been suggested to enhance carbohydrate delivery via hydrogel formation, but the influence on exogenous carbohydrate oxidation remains unknown. The primary aim of this study was to assess the effects of MAL + FRU + PEC + ALG on exogenous carbohydrate oxidation during exercise compared with a maltodextrin-fructose mixture (MAL + FRU). MAL + FRU has been well established to increase exogenous carbohydrate oxidation during cycling compared with glucose-based carbohydrates (MAL + GLU). However, much evidence focuses on cycling, and direct evidence in running is lacking. Therefore, a secondary aim was to compare exogenous carbohydrate oxidation rates with MAL + FRU versus MAL + GLU during running. Methods: Nine trained runners completed two trials (MAL + FRU and MAL + FRU + PEC + ALG) in a double-blind, randomized crossover design. A subset (n = 7) also completed a MAL + GLU trial to address the secondary aim, and a water trial to establish background expired 13CO2 enrichment. Participants ran at 60% V.O2peak for 120 min while ingesting either water only or carbohydrate solutions at a rate of 1.5 g carbohydrate per minute. Results: At the end of 120 min of exercise, exogenous carbohydrate oxidation rates were 0.9 (SD 0.5) g/min with MAL + GLU ingestion. MAL + FRU ingestion increased exogenous carbohydrate oxidation rates to 1.1 (SD 0.3) g·min-1 (P = 0.038), with no further increase with MAL + FRU + PEC + ALG ingestion (1.1 (SD 0.3) g/min; P = 1.0). No time-treatment interaction effects were observed for plasma glucose, lactate, insulin, or nonesterified fatty acids, or for ratings of perceived exertion or gastrointestinal symptoms (all, P > 0.05). Conclusion: To maximize exogenous carbohydrate oxidation during moderate-intensity running, athletes may benefit from consuming glucose(polymer)-fructose mixtures over glucose-based carbohydrates alone, but the addition of pectin and sodium alginate offers no further benefit.